2006
DOI: 10.1021/ie051209u
|View full text |Cite
|
Sign up to set email alerts
|

Acid Neutralization by Marine Cylinder Lubricants Inside a Heating Capillary:  Strong/Weak-Stick Collision Mechanisms

Abstract: Base nanoparticles are present in marine cylinder lubricants (MCLs) for controlling cylinder corrosive wear by neutralizing combustion-generated acids. A portion of the surfactants stabilizing these nanoparticles may have dynamic properties, upon which strong/weak-stick collisions are proposed to drive the interaction between base particles and acid drops in oil media. Neutralization of sulfuric acid droplets (150-200 µm in diameter) by MCL samples (with a base number of BN ) 70 mg KOH/g oil) was performed ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…The MD simulations of nanoparticle adsorption onto a water droplet are the first of their kind and give support for the neutralization mechanism proposed by Fu and co-workers, 15,20 which involves some surfactant (in the sulfonate case) transferring onto the water overbased particle which would surely increase the neutralization rate. 54 Potential of mean force, PMF, calculations indicate 25 that the detachment free energy of the nanoparticle is greatest for the sulfonate and least for the salicylate, suggesting that the former particles will be the fastest to react.…”
Section: Nanoparticle-water Droplet Associationsupporting
confidence: 61%
“…The MD simulations of nanoparticle adsorption onto a water droplet are the first of their kind and give support for the neutralization mechanism proposed by Fu and co-workers, 15,20 which involves some surfactant (in the sulfonate case) transferring onto the water overbased particle which would surely increase the neutralization rate. 54 Potential of mean force, PMF, calculations indicate 25 that the detachment free energy of the nanoparticle is greatest for the sulfonate and least for the salicylate, suggesting that the former particles will be the fastest to react.…”
Section: Nanoparticle-water Droplet Associationsupporting
confidence: 61%
“…However, different 7 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 locations for the reaction products has been noted in the literature. 21,25,31,34 Fu et al 25 observed four different reaction behaviors in different lube oil formulations within a temperature range 25-170 о C, and attributed these differences to different lube oil formulations, temperatures, and overbased detergents. The observed reaction behaviors were explained by a strong/weak-stick collision mechanism in which the neutralization rate is enhanced by formulating lube oils with a high frequency of strong-stick collisions.…”
Section: Neutralization Mechanism and Rate-limiting Stepsmentioning
confidence: 99%
“…Wu et al 20 observed the formation of crystals (CaSO 4 from the neutralization reaction), which may deposit on the surface of the H 2 SO 4 droplet, inhibiting further reaction (i.e., desorption-control). However, the occurrence of crystal formation depends on the lube oil formulation; 25 the reaction products may be solubilized into the lube oil if the lube oil is formulated with the suitable dispersants. Assuming that a stable emulsion is formed when H 2 SO 4 is introduced into the lube oil (droplet radii in the range 1-10 µm 45 ), it is expected that inhibition by CaSO 4 crystal formation is not a concern.…”
mentioning
confidence: 99%
“…Since most condensed sulfuric acid is expected at the lower part of the cylinder liner where the temperature is relatively low [22], an explanation of the higher corrosive wear at the TDC is that the upward motion of the piston entrains the condensed acids into the lubricating film and collects them above the top piston ring. When the piston reaches the vicinity of the TDC, the region above the top piston ring between the cylinder liner and the piston may be the place where most acid droplets are collected, thus promoting the strongest Ostwald ripening.…”
Section: Resultsmentioning
confidence: 99%
“…Formulating lubricant oils with overbased additives has been proven to be the most effective means against the corrosive wear of engine parts [8], and interest in the continuous improvement of overbased detergents is growing due to more severe conditions of modern engines and stricter environmental regulations [15][16][17][18]. Recently, several reports have shed light on understanding how acids are neutralized by overbased nanoparticles in oil media [19][20][21][22]. However, the complete picture and all mechanisms of the acid corrosion of the engine cylinder are still not known.…”
Section: Introductionmentioning
confidence: 99%